Using Real Options Approach to Risk and Uncertainty in Wind Power Plant Valuation - Biyikli, Duygu; Sesli, Faik Ahmet; Kasap, Pelin (Springer Science and Business Media LLC, 2024)
Abstract
Since the future cannot be predicted clearly, each parameter value in investment is variable within probabilities. Costs, expenses, inflation rate, unit prices, government support, and incentives or income amount contain risks and uncertainties for every investment. While these risks and uncertainties decrease the investment value in traditional valuation, they increase the value in real options. Investors may also want to defer, expand, or abandon the investment according to market conditions. These flexibility factors offered by real options for large-budget investments such as Wind Power Plants (WPPs) also add extra value to the investment. This study aimed to investigate how the flexibility situations predicted for this WPP with positive Net Present Value (NPV) affect the investment. In particular, the defer option was applied in two different ways. First, the return scarcity parameter was used to calculate the opportunity cost lost to competitors due to differences. Secondly, this loss was applied as a numerical change to cash flows. In the application where the return scarcity parameter was used, the results obtained with the Black-Scholes and Binomial methods were quite different from each other. In the second application, the loss percentage applied to cash flows, although higher than the return scarcity parameter, returned more positive results. The fact that the return scarcity parameter gave very low results, especially with the Black-Scholes method, was also an important result for the literature on the use of the defer option. In addition, the demonstration of the extra value that real options bring to investments was another important result for the increase in the installation of renewable energy plants and the use of clean energy in line with the UN Sustainable Development Goals.